Tıp 1 dıyabetes mellitus tanısı olan ergenlerde yatışı olan ve olmayan hastaların benlik saygısı ve aile tutumlarının karşılaştırlması - AFSHORD, TELLI ZADEHGAN (My University, 2021)
Introduction: Type 1 Diabetes Mellitus (T1 DM) disease as one of the most common chronic diseases known in children and adolescents and therefore represents important health problems in this population. Children and adolescents who was diagnosed with T1DM, the disease should be approached as a whole, and the psychological status, adaptation difficulties and attitudes of the patients and their caregivers, which significantly affect the treatment compliance, should be evaluated as well as the physical dimension. We aimed to assess self-esteem and parenting attitudes in Type 1 DM children and adolescent patients with and without treatment compliance. Subjects and Methods: The ethics committee approval of the study is obtained, then the study was carried out descriptively in pediatric endocrinology clinics of Bezmialem Vakıf University hospital, 40 T1DM diagnosed children and adolescents aged 12-18 years, who has hospitalization for DM compliance problems accepted to participate in the study were chosen as study groups and 38 children and adolescents who were followed up with a diagnosis of T1DM without hospitalization in pediatric endocrinology outpatient clinic and accepted to be included in the study were selected as the control group. After obtaining the informed consent form for both groups, a data collection form including sociodemographic information was filled by the researcher. In the psychiatric evaluation, the diagnoses were made by the researcher in the Schedule for Affective Disorders and Schizophrenia for School Aged Children Kiddie-SADS-lifetime Version (K-SADS-PL) semi-structured interview, and the participants were also asked to fill in the Parental Attitude Scale and the Coopersmith Self-Esteem Inventory. Results: The age and gender of the patients in the case and control groups of our study did not differ significantly (p> 0.05). The mean age at diagnosis was found to be 8.5 ± 4.1 in the case group and 10.6 ± 3.1 in the control group, and as a result, the age of diagnosis in the case group was found to be significantly lower than the control group (p = 0.023). In this study, the mean last HbA1c levels of the case group were 9.4 ± 2.1 and the mean last HbA1c value of the control group was 7.6 ± 1.2, and this value was found to be statistically significantly higher in the case group (p<0.001). K-SADS-PL-DSM-5 semi-structured psychiatric evaluation results were determined as more depression diagnosis, Generalized Anxiety Disorder and Social Phobia diagnosis in the case group (depression p <0.001), (generalized anxiety p<0.001), (social phobia p = 0.011). It was determined that 76.2% of the mothers in the case group showed democratic attitude and 23.8% authoritarian attitude. In this group, the attitude of fathers is 69.0% democrat and 31.0% authoritarian. In the control group, 92% of the mothers were democratic and 7.9% were authoritarian, 84.2% of the fathers were democratic and 15.8% were authoritarian. Comparison of groups showed that authoritarian parental attitude was significantly higher in the case group (Mother Democrat p = 0.006), (Father Democrat p = 0.023). Looking at the mean scores distribution of the sub-dimension of the Coopersmith Self-Esteem Inventory, the self-esteem and general scores of the case group participants were found to be significantly lower than the control group, and similarly, the home-family self-esteem score showed a significant difference (full score p = 0.007), (overall score p = 0.048 ), (family home score p = 0.002). Conclusion: In our study, the relationship between poor metabolic control and inappropriate treatment compliance of T1DM in child and adolescents with their low self-esteem and authoritarian attitude of their parents has been determind. In addition, the high rates of pshychiatric disorders which determined in the study group with poor metabolic control show that T1DM is not only a physical disease, but also negatively affects the psychological, social and emotional functionality of the individuals. Keywords: Type 1 diyabetes mellitus, self steem, authoritarian parentin style, pscychiyatric disorders
Self-esteem and family attitudes in TYPE 1 DM adolescent patients with and without treatment compliance
Giriş: Tip 1 Diyabetes Mellitus (DM) hastalığı çocuk ve ergenlerde bilinen en yaygın kronik hastalıklar arasında tanımlanmaktadır ve bu nedenle bu popülasyonda önemli sağlık problemlerini temsil etmektedir. T1DM tanısı olan çocuk ve ergenlerde hastalık bütüncül olarak ele alınmalıdır, fiziksel boyutunun yanında tedavi uyumunu önemli derece etkileyen hasta ve bakım verenlerinin psikolojik durumları, uyum güçlükleri ve hastalığa yaklaşımları da değerlendirilmelidir. Bu çalışmada yatış gerekliği olan ve olmayan hastaların arasında hastanın benlik saygı düzeyi ve anne baba tutumunun tedavi uyumunda ön görücü olup olmadığının araştırılması amaçlanmıştır. Gereç ve Yöntem: Çalışmanın etik kurul onayından sonra Bezmialem Vakıf Üniversitesi Hastanesi Çocuk Endokrinologi servisinde tip 1 diyabet tanısıyla yatışı olan ve çalışmaya katılmayı kabul eden 12-18 yaş arası 40 çocuk ve ergen vaka grubu olarak ve yaş ve cinsiyet açısından benzer özellikler gösteren, çocuk endokrinoloji polikliniğinde yatışları olmadan T1DM tanısıyla takip edilen ve çalışmaya dahil olmayı kabul eden 38 çocuk ve ergen kontrol grubu olarak alınmıştır. Her iki grupta aydınlatılmış onay formu alındıktan sonra araştırmacı tarafından sosyodemografik özelliklerinin yer aldığı bir veri toplama form doldurulmuştur. Psikiyatrik bozukluklar tanıları yarı yapılandırılmış Okul Çağı Çocukları için Duygulanım Bozuklukları ve Şizofreni Görüşme Çizelgesi- Şimdi ve Yaşam Boyu Versiyonuyla (ÇDŞG-ŞY) araştırmacı tarafından değerlendirilmiştir ayrıca katılımcılardan Anne Baba Tutum Ölçeği (ABTÖ) ve Coopersmith Benlik Saygı Envanterinin doldurulması istenmiştir. Bulgular: Çalışmamızın vaka ve kontrol grubunda hastaların yaşları ve cinsiyetleri anlamlı farklılık göstermemiştir (p >0.05). Vaka grubunda tanı yaşı ortalama 8.5 ± 4.1 ve kontrol grubunda 10.6 ± 3.1 olarak saptanmıştır ve sonuç olarak vaka grubunda tanı yaşı, kontrol grubundan anlamlı olarak daha düşük tespit edilmiştir (p = 0.023). Çalışmamızda vaka grubunun ortalama son HbA1c düzeyleri 9.4 ± 2.1 ve kontrol grubunun ortalama son HbA1c değeri 7.6 ± 1.2 olarak belirlenmiştir, vaka grubunda bu değer istatistiksel olarak anlamlı derecede yüksek saptanmıştır (p <0.001). ÇDŞG-ŞY-DSM-5 yarı yapılandırılmış psikiyatrik değerlendirme sonuçları vaka grubunda daha fazla Depresyon tanısı, Yaygın Anksiyete Bozukluğu ve Sosyal Fobi tanısı olarak belirlenmiştir (depresyon p <0.001), (yaygın anksiyete p <0.001), (sosyal fobi p = 0.011). Vaka grubunda %76.2 annelerin demokrat tutumu ve %23.8 otoriter tutumu gösterdikleri belirlenmiştir. Bu grupta babaları tutumu %69.0 demokrat ve %31.0 otoriter olarak görülmüştür. Kontrol grubunda annelerin %92'si demokrat ve %7.9'u otoriter tutum sergilerken babaların %84.2'si demokrat tutum ve %15.8'i otoriter tutum göstermişler. Guruplar arası karşılaştırmada anlamlı olarak vaka grubunda otoriter anne baba tutumu daha fazla görülmüştür (Anne Demokrat p=0.006), (Baba Demokrat p= 0.023). Coopersmith Benlik Saygı Envanterinin alt boyut puan ortalamalarının dağılımına bakıldığında vaka grubu katılımcıların benlik saygı tam ve genel puanı kontrol grubundan anlamlı olarak düşük bulunmuştur ve benzer şekilde ev aile öz saygı puanı anlamlı farklılık göstermiştir (tam puan p=0.007), (genel puan p= 0.048), (aile ev puan p=0.002). Sonuç: Çalışmamızda, kronik bir hastalık olan T1DM'in kötü metabolik kontrol ve uygun düzeyde olmayan tedavi uyumu ile çocuk ve ergenlerin düşük benlik saygısı ve yaşadığı ailede otoriter anne baba tutumuyla ilişkisi gösterilmiştir. Ayrıca bu çalışmada metabolik kontrolü kötü giden vaka grubunda elde ettiğimiz yüksek ruhsal hastalık oranları, T1DM'in sadece fiziksel bir hastalık olmadığını, bireyin psikolojik, sosyal, emosyonel işlevselliğini de olumsuz etkilediğini düşünülmüştür. Anahtar Kelimeler: T1DM, benlik saygısı, otoriter anne baba tutumu, psikiyatrik tanı
Keywords: MEDICINE; Çocuk sağlığı ve hastalıkları